Periodontal Wound Healing and Regeneration: Insights for Engineering New Therapeutic Approaches - Fraser, David; Caton, Jack; Benoit, Danielle S. W. (Frontiers in Dental Medicine, 2022)
Periodontitis is a widespread inflammatory disease that leads to loss of the tooth supporting periodontal tissues. The few therapies available to regenerate periodontal tissues have high costs and inherent limitations, inspiring the development of new approaches. Studies have shown that periodontal tissues have an inherent capacity for regeneration, driven by multipotent cells residing in the periodontal ligament (PDL). The purpose of this review is to describe the current understanding of the mechanisms driving periodontal wound healing and regeneration that can inform the development of new treatment approaches. The biologic basis underlying established therapies such as guided tissue regeneration (GTR) and growth factor delivery are reviewed, along with examples of biomaterials that have been engineered to improve the effectiveness of these approaches. Emerging therapies such as those targeting Wnt signaling, periodontal cell delivery or recruitment, and tissue engineered scaffolds are described in the context of periodontal wound healing, using key in vivo studies to illustrate the impact these approaches can have on the formation of new cementum, alveolar bone, and PDL. Finally, design principles for engineering new therapies are suggested which build on current knowledge of periodontal wound healing and regeneration.